Paródia e carnavalização no cancioneiro Chico Buarque de Hollanda - OLIVEIRA, Paula Cristhiane da Silva (Universidade Federal do Pará, 2014)
Research and “Parody in carnivalization Songbook Chico Buarque” investigates aspects parodic and carnival present in the repertoire of Chico Buarque, emphasizing Carnivalization initially as a medieval cultural practice, based on the theories of Mikhail Bakhtin, about Mardi Gras Medieval and Renaissance analyzed in the work of François Rabelais, propositions developed in the book The popular culture: in the Middle Ages and Renaissance. In this analysis, this study highlights the main constituent elements of carnival rituals: 1)dialogism between popular discourse and poetic discourse, since all communication is a reciprocal action; 2)the carnivalesque ambivalence of language that prevail for establishing the connection between the positive and negative poles for the birth-death cycle; 3)laughter and their meanings and complexities of accomplishments ranging from the ingenuity and satire, and finally; 4) the parody that incorporates all the elements cited above for its realization. From the apprehension of these concepts will also outline a brief historical overview to understand the many facets of artistic Chico Buarque and its relation to social life in order to see it through its social production as a lyric poet. And to prove the importance of universal carnival culture, emphasizing the Brazilian culture, the songs has more samba (1964), Dream of a Carnival (1965), Tomorrow, nobody knows (1966), Night of the masked (1966), Wheel Jellyfish (1967), She desatinou (1968), While You (1970), When the carnival there (1972) and will pass (1984) will be analyzed in a comparative setting carnival contemporary and medieval carnival, noting the consensus and dissent which are still part of this popular festival. This assessment, this study highlights the importance of the work of Chico Buarque by this cultural and poetic value in all its artistic activities. The judgment of analisy will moderate in study bibliography among Baktin’s theory of carnival and Chico Buarque’s music, which here will be understood with poem-song to emphasize these the thematic of carnival.